Effects on U-Boat Performance of Intelligence from Decryption of Allied Communication - Behrens,Carl E. (1954)
Examination of the War Diary of the German ComSubs has made it possible to estimate the character and extent of intelligence obtained by the decryption of Allied radio messages pertaining to convoy operations in the North Atlantic during World War II, and to determine the effect of such intelligence on the capability of the U-Boats to contact convoys and sink ships. It is estimated that the availability of timely usable decryption intelligence increased the contact rate twofold over that which they would have obtained without it; probably over 60 sinkings in excess of the expected number if they had been deprived of decryption intelligence. These calculations help in estimating a valid measure of the effectiveness of current and future submarines in anti-convoy operations when decryption intelligence is not available. (Author)